Intraoral atypical lentiginous melanocytic lesion in a pediatric patient - Barros de Oliveira, Analú [UNESP]; Morandin Ferrisse, Túlio [UNESP]; Albergoni Silveira, Heitor [UNESP]; Vilela Silva, Evanio [UNESP]; Bufalino, Andreia [UNESP]; Esquiche León, Jorge; Lourenção Brighenti, Fernanda [UNESP] (Elsevier, 2021)
We present a rare case of intraoral atypical lentiginous melanocytic lesion affecting a pediatric patient, in which the diagnosis of lentiginous junctional melanocytic nevus with cytologic atypia was favored. The main differential diagnosis is lentiginous melanoma, which is a slowly progressing lesion, affecting mainly older adults, and microscopically presenting lentiginous growth pattern of moderately atypical melanocytes, with focal nesting and pagetoid spread. It is strongly recommended that melanocytic lesions showing features of atypical lentiginous growth pattern should be treated with wide excision; however, the impact of these guidelines on pediatric patients needs to be better defined with the report of further cases.
Keywords: Atypical lentiginous melanocytic hyperplasia; Atypical lentiginous melanocytic nevus; Melanocytic nevus; Melanoma; Oral cavity; Pediatric patient